A Review of Selumetinib in the Treatment of Neurofibromatosis Type 1–Related Plexiform Neurofibromas. Issue 6 (June 2022) - Anderson, Mary Kate; Johnson, Meredith; Thornburg, Lauren; Halford, Zachery
Objective: To evaluate the safety and efficacy of selumetinib, a novel MEK inhibitor, for the treatment of plexiform neurofibromas (PN) in patients with neurofibromatosis type 1 (NF1). Data Sources: An English-based literature search of PubMed, EMBASE, and ClinicalTrials.gov was conducted using the terms selumetinib AND neurofibromatosis from inception to August 1, 2021. Study Selection and Data Extraction: Relevant prescribing information, abstracts, and articles identified through the search were considered for inclusion in this review. Data Synthesis: The open-label, multicenter, single-arm, phase II SPRINT trial demonstrated clinically significant improvements in PN-related complications. Of 50 symptomatic patients, 68% experienced a partial response, with a median change in tumor volume of −27.9% from baseline. Estimated progression-free survival at 3 years was 84%. Additionally, clinically meaningful improvements were seen on patient- and parent-reported assessments evaluating pain, range of motion, disfigurement, and quality of life. Overall, the adverse effect profile for selumetinib appears mild and manageable. Relevance to Patient Care and Clinical Practice: Selumetinib is the first FDA-approved treatment for inoperable PN in patients with NF1, demonstrating that MEK inhibition is a promising therapeutic strategy. Studies are ongoing to assess the effect of selumetinib on other NF1-associated tumor types and to determine the optimal dosing schedule and treatment duration. Cost and treatment burden must be considered when selecting selumetinib therapy. Conclusion: Selumetinib exhibits impressive antitumor activity and sustained clinical benefit in patients lacking other viable treatment options. Further studies are warranted to determine the optimal age of initiation, treatment duration, and overall cost-effectiveness of selumetinib.